Biology and description of Megaprosternum cleonarovorum sp. nov. Hymenoptera: Bethylidae) a gregarious larval ectoparasitoid of Cleonaria bicolor Thomson (Coleoptera: Cerambycidae) from India - Gupta, Ankita; Rajeshwari, S. K.; Azevedo, Celso O. (Zootaxa, 2017)
Megaprosternum Azevedo (Bethylidae: Scleroderminae) is newly recorded from the Oriental region, and M. cleonarovorum Gupta & Azevedo sp. nov. is described and illustrated from Southern India as a gregarious larval ectoparasitoid of Cleonaria bicolor Thomson (Coleoptera: Cerambycidae) on the host plant Ixora coccinea L. (Rubiacae). This is the first ever documentation of the biology of Megaprosternum Azevedo.